(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2024)
This article deals with the evolution of laws, on grounds of the philosophy of Charles Sanders Peirce who, despite considering himself a logician, dedicated himself to several areas of science, such as mathematics, physics, astronomy, chemistry, psychology, history, linguistics, logic and philosophy, always seeking knowledge of methods and their logical foundations. To this end, we made a succinct introduction to some of the main concepts that the philosopher architecturally constructed in a triadic structure, which supports his entire philosophy, which is based on Phenomenology (Falibilism, Synechism, Pragmatism, among others). On the basis of this philosophical foundation, a dialog is held with the theme of the evolutionary nature of legislation, based on an analysis of the continuity between chance and law, which is very relevant to the construction of our society.